2022
DOI: 10.1186/s44149-022-00063-7
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial resistance and molecular typing of Salmonella in the chicken production chain in Hubei Province, China

Abstract: Salmonella is a significant foodborne zoonotic pathogen that endangers both human and animal health. The goal of this research is to gain a preliminary understanding of Salmonella contamination and antimicrobial resistance in the chicken production chain in Hubei Province, China. 1149 animal and environmental samples were collected from chicken farms, slaughterhouses, and retail markets in six cities across Hubei Province in China from 2019 to 2020, yielding Salmonella isolation rates of 4.68% (28/598), 12.21%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Our E. coli isolates from China, showed a diverse phylogeny with phylogroups A and B predominating as well as group C-G appearing at lower prevalence across all provinces; this has been similarly observed in other studies of healthy chickens conducted globally (46,47). There are fewer large scale surveillance studies for S. enterica, but a recent study of 91 Salmonella strains isolated from chicken farms, slaughterhouses and abattoirs in the Hubei province of China showed a more diverse phylogeny than ours, with 27 different serotypes isolated (48). Similarly another study from a single farm and connected slaughterhouse in Sichuan Province identified seven serotypes over three production cycles (49).…”
Section: Discussionsupporting
confidence: 87%
“…Our E. coli isolates from China, showed a diverse phylogeny with phylogroups A and B predominating as well as group C-G appearing at lower prevalence across all provinces; this has been similarly observed in other studies of healthy chickens conducted globally (46,47). There are fewer large scale surveillance studies for S. enterica, but a recent study of 91 Salmonella strains isolated from chicken farms, slaughterhouses and abattoirs in the Hubei province of China showed a more diverse phylogeny than ours, with 27 different serotypes isolated (48). Similarly another study from a single farm and connected slaughterhouse in Sichuan Province identified seven serotypes over three production cycles (49).…”
Section: Discussionsupporting
confidence: 87%